The Onset of Eosinophilic Pneumonia Preceding Anti-synthetase Syndrome - Hachisu, Yoshimasa (Intern Med, 2017)
A 66-year-old man had been treated with prednisolone for eosinophilic pneumonia for 8 years. His slowly progressing cough and dyspnea were accompanied by elevated levels of fibrotic serological markers and an increased reticular shadow on chest computed tomography images. The patient had recently tested positive for anti-EJ antibodies, a type of anti-aminoacyl-tRNA synthetase antibody; therefore, we diagnosed him with an exacerbation of interstitial pneumonia due to anti-synthetase syndrome (ASS). He was treated with tacrolimus and an increased prednisolone dosage. We herein present the first reported case of eosinophilic pneumonia preceding anti-EJ antibody-positive ASS.